Population genetics of two sibling species of fiddler crabs (Decapoda, Ocypodidae): Brazilian homogeneity and West Atlantic heterogeneity - Rodrigues, Renata De Oliveira [UNESP]; Trettin, Ivana Miranda [UNESP]; Costa, Tânia Marcia [UNESP]; Schubart, Christoph D. (Brill Academic Publishers, 2024)
Fiddler crabs are a widespread group of marine invertebrates. Their wide distribution is due to the great capacity of their larvae to disperse among estuarine and shelf waters. Therefore, it is expected that all populations along their distribution show molecular similarities due to extensive gene flow. Thus, we assessed the intra- and interspecific genetic divergence of two sibling species of fiddler crabs, Minuca panema and Minuca mordax, based on COI mtDNA sequences. The molecular data resulted in a highly mixed haplotype network for M. panema, while M. mordax sequences were clustered in two groups, one with Brazilian and other with Costa Rican haplotypes. The highest variance in M. panema was found within populations, while in M. mordax it was between groups and populations. The analyses of nucleotide divergence showed small genetic variance within populations of both species and between Brazilian populations, and higher variance between Brazilian and Costa Rican populations of M. mordax. The highest genetic divergence was found between the two species. Thereby, our results show an intense gene flow along the Brazilian coast, while there is a clear divergence among Brazil and Costa Rica, which may be a result of the great distance between these populations.
Keywords: Minuca mordax; Minuca panema; nucleotide divergence; Phylogeny